PW 0427 Costs of unintentional injuries among children in an urban slum community in kampala city, uganda. (November 2018) - Mukama, Trasias; Ssemugabo, Charles; Halage, Abdullah Ali; Gibson, Dustin; Ndejjo, Rawlance; Ssempebwa, John; Kobusingye, Olive
Abstract : Introduction: Unintentional injuries burden communities' worldwide causing deaths, disability, productivity and financial losses and disproportionately affect children in low-income settings but their cost on communities remains under studied. This study aimed to determine direct and indirect costs of unintentional childhood injuries in a resource deprived community. Methods: We used a cross-sectional household survey design in Kasubi, a Kampala city slum. We collected data on occurrence and associated costs for a one-year period from July 2014 to June 2015. Data was entered in Epidata 3.02 and analyzed in Stata 13.0 statistical software. Descriptive and bivariate analysis were conducted to identify risk factors for injury, cost-estimates of injuries by severity, cause and nature. Results: A total of 706 (44.7%) children who had suffered from injuries were reported in the one year period. More male children, (n=415, 58.7%) suffered injuries than females (n=291, 41.2%). The average out-of-pocket expenditure on treating an injury was US $24.1 (standard deviation [SD]=±$62.8) and mean school days lost was 25.1 days (SD=±51.8). Road traffic injuries (RTIs) resulted in higher costs (mean difference was US $51.1 (95% CI: $11.4 to $90.8) compared to injuries that occurred at school. Also, road traffic related injuries (mean difference=39.4; 95% CI: 13.1 to 65.7) resulted in significantly more school days lost compared to falls. Conclusion: In a slum community within Uganda, unintentional childhood injuries resulted in high out-of-pocket expenditures and missed school attendance and the cost varied widely amongst the cases. These findings highlight the need to invest in population level injury prevention interventions to reduce household expenditure by poor households on injury treatment.